TEKNIK VOKAL PADA GAYA DENDANG MINANGKABAU DALAM LAGU “GABAK DILANGIK HUJAN TAK TURUN” MISRAMOLAI - Agit Anriani; Robby Ferdian (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This study aims to identify and analyze vocal techniques in the Minangkabau dendang style as performed in the song Gabak di Langik Hujan Tak Turun, sung by Misramolai, a legendary Minangkabau singer. This song was chosen as the object of study because it is considered to employ vocal techniques that differ from those found in popular music genres such as Indonesian pop, Minang pop, and dangdut. The research employs a qualitative descriptive method with a field study approach. Data collection techniques include video observation, direct interviews with Misramolai, literature review, and documentation. The findings show that Misramolai uses chest breathing techniques as an adaptation to the tempo and short lyrical phrases of the song, as well as focusing vocal resonance in the throat cavity to produce a distinct vocal character. Intonation is maintained through gradual training to ensure pitch stability despite melodic fluctuations, while articulation is executed with clear vocal delivery to preserve the clarity of the lyrics’ meaning. Additionally, typical dendang Minang techniques such as garinyiak (pangka, tangah, ujuang) and gadiiek are consistently applied, demonstrating both technical skill and deep emotional expression.